THE EFFECT OF PRIOR EXPERIENCE AND TRUST ON CUSTOMER LOYALTY WITH SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY ON CUSTOMERS OF PT. PEGADAIAN BRANCH OF TEBING TINGGI CITY) - Yomeini Margareth; Suci Etri Jayanti; Rumiris Siahaan (RADJA PUBLIKA, 2023)
This study aims to find out how the influence of Prior Experience and Trust on Customer Loyalty with Satisfaction as an Intervening Variable (Case Study on Customers of PT. Pawnshop, Tebing Tinggi City Branch). The population in this study are all customers of PT. Tebing Tinggi Branch Pawnshop. In determining the sample used the slovin formula with purposive sampling technique, samples taken were 91 respondents. The analytical tool in this study used data processing using IBM SPSS 25.00 for windows. The results of testing the hypothesis using the t test (partial) and to test the intervening variables the researcher uses the path analysis method (path analysis). From this test it can be concluded that based on the results of the analysis of hypothesis 1 it can be seen that tcount (3.584) >